Task-based language education : (Cambridge University Press, 2006)
ask-based language teaching is an approach which differs from traditional approaches by emphasising the importance of engaging learners' natural abilities for acquiring language incidentally through the performance of tasks that draw learners' attention to form. Drawing on the multiple perspectives and expertise of five leading authorities in the field, this book provides a comprehensive and balanced account of task-based language teaching (TBLT). Split into five sections, the book provides an historical account of the development of TBLT and introduces the key issues facing the area. A number of different theoretical perspectives that have informed TBLT are presented, followed by a discussion on key pedagogic aspects - syllabus design, methodology of a task-based lesson, and task-based assessment. The final sections consider the research that has investigated the effectiveness of TBLT, addresses critiques and suggest directions for future research. Task-based language teaching is now mandated by many educational authorities throughout the world and this book serves as a core source of information for researchers, teachers and students.